Effect of Plant Age on Fresh Rhizome Yield and Volatile Oil Composition of Acorus calamus Linn. (University of Khartoum Journal of Agricultural Sciences, 2025)
The effect of plant age on growth, yield and oil content andcomposition of sweet flag (Acorus calamus) was studied in fourpopulations at four different ages, raised at CIMAP ExperimentalResearch Farm, India. The plant age had significant effect on total freshyield and leaves and rhizomes fresh weights. These parameters showedincreasing trend with advancement of harvesting age up to 6 years, andage increase to more than 15 years resulted in their decrease. Significantlyhighest number of shoots per square metre was recorded in more than 15-year old crop, and the lowest number was recorded in the 6-year old crop.The highest oil yield of rhizomes was obtained from the six-year oldplants. Shoot length, rhizome: leaf ratio (R/L) and oil yield of leaves didnot show significant differences with the age of the plant. However, 6-year old plants recorded the highest average shoot length, and the three-year old plants gave the highest oil yield of leaves. The total fresh yieldshowed a highly significant positive correlation with rhizomes freshweight (r=0.999), leaves fresh weight (r= 0.994) and with rhizome: leafratio (r= 0.998). Highly significant positive correlations (r=0.999) werealso obtained between rhizomes oil content and rhizomes oil yield andbetween leaves oil content and leaves oil yield. β-asarone was the mostdominant constituent in the oils of both leaves and rhizomes, constitutingan average of 84.2% in the leaves and 88.9% in the rhizomes oil. Thestudy indicated that the oil content of fresh rhizomes and leaves is themain contributor to their oil yields, and selection for high oil content willbe effective. The constituents of the volatile oil remained the sameirrespective of the plant age.